Subjective aspects of hypochondria - García-Arroyo, José Manuel (2021)
Objectives: An attempt to focus on the subjective aspects of hypochondriasis, which are not sufficiently clarified in modern literature, probably due to the almost exclusive consideration of the external (behavioral) manifestations provided by the patients and disregarding more personal aspects. Material and Methods: Twelve patients with the diagnosis of Hypocondriasis (ICD-10), seen in consult at the Seville (Spain) Asociación de Psicopatología y  Psicoanálisis  (APPS),  were  applied  the  Subjectivity Approach  Method  (MAS).  By  expressing  themselves verbally in interviews, they analytically broke down their problems into different elements; the statements thus obtained are grouped into categories that define and put in evidence expected subjective components.  Results: The exaggerated intensity of physical sensations, the abnormal attentional direction, and the attribution of wrong meanings are elements that interact and form a “loop”, a knot or a circle impossible to escape from. The use of the “square of Apuleius” helps to visualize how the affected individuals keep their body above all, so that the vectors necessarily converge in it; this explains why they can’t access to a real encounter with others and thus, suffer some social deterioration. Conclusions: The subjective clues drawn here can serve as a compass for any mental health professional working in psychotherapy with hypochondriac patients.